Ocean Clean Laundry / Faaret Abd Ghani ... [et al.] - Abd Ghani, Faaret; Mat Saad, Lily Diana; Zainal Abidin, Maizatul Aqma; Nasir, Mohd Khairi (Faculty of Communication and Media Studies, 2005)
Ocean Clean is a partnership business, which is shared with five members. Each partner organized one position such as General Manager, Administration Manager, Marketing Manager, Operation Manager, and Financial Manager. Each organization plays big part to make sure this business running smoothly. In addition, each manager has to know the entire work, so that means we are deeply known the shaped of the business, the problem that we have to faced and this will make us to managing this business effectively.